Assessing barriers to health insurance and threats to equity in comparative perspective: The Health Insurance Access Database - Quesnel-Vallée Amélie; Renahy Emilie; Jenkins Tania; Cerigo Helen (BMC, 2012)
Abstract Background Typologies traditionally used for international comparisons of health systems often conflate many system characteristics. To capture policy changes over time and by service in health systems regulation of public and private insurance, we propose a database containing explicit, standardized indicators of policy instruments. Methods The Health Insurance Access Database (HIAD) will collect policy information for ten OECD countries, over a range of eight health services, from 1990-2010. Policy indicators were selected through a comprehensive literature review which identified policy instruments most likely to constitute barriers to health insurance, thus potentially posing a threat to equity. As data collection is still underway, we present here the theoretical bases and methodology adopted, with a focus on the rationale underpinning the study instruments. Results These harmonized data will allow the capture of policy changes in health systems regulation of public and private insurance over time and by service. The standardization process will permit international comparisons of systems' performance with regards to health insurance access and equity. Conclusion This research will inform and feed the current debate on the future of health care in developed countries and on the role of the private sector in these changes.